Diagnostic methods and clinical repercussions of Fetal Alcohol Syndrome (Research, Society and Development, 2023)
The consumption of alcoholic beverages results in harm to the individual who ingests it and also to associates, such as, for example, fetuses of mothers who use such a substance. It is extremely important to understand that alcohol is a teratogen and can easily cross the placenta, consequently the fetus receives the substance in its system and, because it has a reduced metabolism, alcohol remains in the fetal bloodstream for a longer time. Thus, the baby is born with irreversible damage and systemic complications, mainly neurological, making it impossible for the child to develop properly. This set of complications is known as Fetal Alcohol Syndrome. Early diagnosis is of paramount importance for monitoring and reducing complications, however, many professionals still have difficulty recognizing the syndrome and making the diagnosis. Based on this question, the objective of the research was to investigate the main diagnostic methods used to identify fetal alcohol syndrome. The methodology used was an integrative review, analyzing previous and recent studies to understand the subject. 15 articles were analyzed, where physical and mental damage caused by the use of alcohol by the pregnant woman to the fetus was observed, in addition, criteria that can help health professionals in the diagnosis were described. It is concluded that health education is the main prevention, in addition, the doctor-patient relationship is of great importance for early diagnosis, before birth and creation of health strategies after it.